HIV and risk environment for injecting drug users: the past, present, and future - Strathdee, Steffanie A; Hallett, Timothy B; Bobrova, Natalia; Rhodes, Tim; Booth, Robert; Abdool, Reychad; Hankins, Catherine A (The Lancet (British edition), 2010)
We systematically reviewed reports about determinants of HIV infection in injecting drug users from 2000 to 2009, classifying findings by type of environmental influence. We then modelled changes in risk environments in regions with severe HIV epidemics associated with injecting drug use. Of 94 studies identified, 25 intentionally examined risk environments. Modelling of HIV epidemics showed substantial heterogeneity in the number of HIV infections that are attributed to injecting drug use and unprotected sex. We estimate that, during 2010–15, HIV prevalence could be reduced by 41% in Odessa (Ukraine), 43% in Karachi (Pakistan), and 30% in Nairobi (Kenya) through a 60% reduction of the unmet need of programmes for opioid substitution, needle exchange, and antiretroviral therapy. Mitigation of patient transition to injecting drugs from non-injecting forms could avert a 98% increase in HIV infections in Karachi; whereas elimination of laws prohibiting opioid substitution with concomitant scale-up could prevent 14% of HIV infections in Nairobi. Optimisation of effectiveness and coverage of interventions is crucial for regions with rapidly growing epidemics. Delineation of environmental risk factors provides a crucial insight into HIV prevention. Evidence-informed, rights-based, combination interventions protecting IDUs' access to HIV prevention and treatment could substantially curtail HIV epidemics.